Hepatitis E virus (HEV): seroprevalence and HEV RNA detection in subjects attending a sexually transmitted infection clinic in Brussels, Belgium - DAUBY, N.; SUIN, V.; JACQUES, M.; ABADY, M.; VAN DEN WIJNGAERT, S.; DELFORGE, M.; DE WIT, S.; LIBOIS, A. (Epidemiology and infection, 2017)
Men who have sex with men (MSM) have an increased incidence of pathogens transmitted by the oro-fecal route. Hepatitis E virus (HEV) is an emerging cause of acute hepatitis and fecal shedding is observed during primary infection. We investigated whether MSM are at increased risk of HEV infection. Subjects who attended a sexually transmitted infection clinic in Brussels and had an HIV test performed between 1 June 2014 and 15 January 2016 were identified. A total of 576 samples were retrospectively screened for both total HEV IgG and HEV RNA. Samples positive for IgG were tested for IgM. MSM proportion was 31·1% (179/576). Overall HEV IgG prevalence was 9·03% (52/576) and was identical in MSM and heterosexual subjects. Among the IgG positive samples, 2/52 (3·84%) samples (both women) were positive for anti-HEV IgM. No sample was positive for HEV RNA. Age over 35 was the only risk factor significantly associated with HEV seropositivity (OR 2·07; 95% CI 1·16–3·67). In conclusion, MSM were not found to have an increased prevalence of HEV as previously reported in other European countries suggesting distinct dynamics of HEV infection in this group across Europe and increased age was associated with a higher risk of seropositivity.